Long-term results after surgical treatment of postinfarction ventricular septal rupture - Takahashi, Hiroaki; Arif, Rawa; Almashhoor, Ali; Ruhparwar, Arjang; Karck, Matthias; Kallenbach, Klaus (European journal of cardio-thoracic surgery, 2015)
OBJECTIVESPostinfarction ventricular septal rupture is a serious complication associated with high hospital mortality rates. The present study aimed to identify predictors of early and late outcome in patients with postinfarction ventricular septal defect over a period of 30 years.METHODSWe retrospectively analysed clinical and operative data, predictors of early mortality and long-term survival in a series of 52 consecutive patients (male, n = 26; mean age, 67 ± 10 years) with postinfarction ventricular septal rupture that was surgically repaired at our institution between September 1982 and December 2012. The overall logistic EuroSCORE was 41 ± 24% and the follow-up rate was 100%.RESULTSThe 30-day mortality rate was 36% (n = 19), and these 19 survivors were followed up for a mean of 7.8 ± 7.7 (median, 6.0) years. The actuarial survival rates of these 19 patients at 1, 5 and 10 years were 91, 75 and 31%, respectively. Univariate predictors of 30-day mortality comprised renal insufficiency, shock at surgery, emergency surgery, logistic EuroSCORE, three-vessel disease, significant left circumflex coronary arterial stenosis, significant right coronary arterial stenosis, incomplete revascularization, surgical duration and cardiopulmonary bypass time and multivariate analysis selected only incomplete coronary revascularization as an independent risk factor of 30-day mortality.CONCLUSIONSEarly mortality rates after surgical repair of postinfarction septal rupture remained poor in this series. Most patients who survived for <30 days had a preoperative shock status. Preoperative improvement in shock status and aggressive coronary revascularization are mandatory for patients with ventricular septal rupture.